Metal-free chemoselective hydrogenation of unsaturated carbon–carbon bonds via cathodic reduction. Issue 14 (10th June 2020) - Qin, Yongwei; Lu, Jingjun; Zou, Zirong; Hong, Huanliang; Li, Yamei; Li, Yibiao; Chen, Lu; Hu, Jinhui; Huang, Yubing
Abstract : A straightforward protocol for efficient and highly selective hydrogenation of unsaturated carbon–carbon bonds via electrochemical reduction has been reported. Abstract : A straightforward protocol for efficient and highly selective hydrogenation of unsaturated carbon–carbon bonds via electrochemical reduction has been reported. A series of chain alkanes and carbonyl compounds are produced under metal-free and external-reductant-free electrolytic conditions. Scale-up experiments have exhibited the potential applications of this protocol in practical synthesis. Deuterium-labelling experiments demonstrate that both DMSO and H2 O in the reaction system can provide hydrogen atoms for the reaction.